Capacity building to facilitate the scaling of the gender-smart accelerator program and foster gender-smart investments in West Africa - Maiga, Mariame; Kpadonou, G. Esaïe; Segnon, Alcade Christel; Derenoncourt, Marie Ena Pascale; Ganyo, Komla Kyky; Lamien, Niéyidouba; Zougmore, Robert Bellarmin (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
As part of the synergy between AICCRA and the West Africa Food System Resilience Program (FSRP), a regional event was conveyed to discuss and identify strategic actions to facilitate the replication of the Gender-Smart Accelerator program in FSRP countries. This deliverable reports the outcomes of the capacity building event to facilitate the scaling of the program in FSRP countries. It outlines key actions identified for scaling the gender-smart accelerator program to and its implementation in FSRP countries